西北冰洋海域表层沉积物中厌氧菌分布特征 - 高爱国; 陈皓文; 赵冬梅 (2009)
用逐步稀释法在4℃和25℃培养条件下测定了西北冰洋海域24个表层沉积物样品中厌氧菌(AnAErObIC bACTErIA,AAb)的检出率和含量.同时,分析了这两项指标的水平分布(纬度间、经度间)差异,以及在不同水深的变化特征.结果表明,在4℃和25℃培养条件下厌氧菌检出率高达100%,AAb含量范围分别为9.00x102~2.40x107CEll·g-1和2.90x104~2.40x107CEll·g-1,平均含量分别为4.54x106CEll·g-1和3.99x106CEll·g-1.AAb含量存在水平分布差异,随着纬度升高,或经度自西向东,或水深的加大,AAb的含量均呈现逐渐降低的趋势. The occurrence and content of anaerobic bacteria in 24 surface sediments in the Western Arctic Ocean were measured via progressive dilution under laboratory incubation at 4℃ and 25℃,and the spatial patterns of anaerobic bacteria distribution were further examined.All the samples have anaerobic bacteria.The contents of anaerobic bacteria cultivated ranged from 9.00×102 to 2.40×107 cell· g-1 wet sample (the same hereafter) and 2.90×104 to 2.40×107 cell· g-1 with an average of 4.54×106 cell· g-1 and 3.99×106 cell· g-1 in the 4℃ and 25℃ samples,respectively.The distributions of anaerobic bacteria varied by both latitude and longitude,and also in sediment samples with different water depths.The anaerobic bacteria content decreased from low latitude to high latitude,from the western area to the eastern area,and from shallow water to deep basin. 国家自然科学基金(No.40576060;40376017) ---